The immature stages of Phylloicus obliquus Navás, 1931 (Insecta: Trichoptera: Calamoceratidae) - Cavalcante, Bruna Maria Silva; Dumas, Leandro Lourenço; Nessimian, Jorge Luiz (Zootaxa, 2020)
Larva and pupa of Phylloicus obliquus Navás are associated, described, illustrated and compared with other Neotropical species of the same genus. The P. obliquus larva differs from the others due to the pattern of distribution of muscle scars on the head, mandibles with two teeth, and a dense row of long yellow setae on the inner margin. The pupa differs from other Phylloicus pupae by the sequence and shape of tergal abdominal hook plates. The case of P. obliquus larvae is composed of rectangular fragments of vegetal material with uniform shape and always arranged in overlapping layers. Larvae were found in a small second order Atlantic Forest stream.